PD-L1 expression on tumor cells and tumor-infiltrating immune cells in thymic epithelial tumors detected with SP142 and SP263 antibodies. - Kei Chubachi; Hisashi Tanaka; Kageaki Taima; Sadatomo Tasaka; Akira Kurose (PLoS ONE)
Introduction Programmed death-ligand 1 (PD-L1) expression in various tumors is known to correlate with the efficacy of immune checkpoint inhibitors; however, evaluation of PD-L1 expression in thymic epithelial tumors (TETs) using multiple antibodies are limited. We retrospectivity evaluated PD-L1 expression in thymomas and thymic carcinomas using two antibodies, SP142 and SP263, and compared their expression rates in each type of TETs. Materials and methods We retrospectively included 37 cases of thymoma and 11 cases of thymic carcinoma that were histologically diagnosed between January 2000 and December 2020. PD-L1 expression was assessed using SP142 and SP263 antibodies with semi-quantitative scoring. Results The concordance rate for PD-L1 positivity between SP142 and SP263 was 81.2%, whereas the concordance rate for high PD-L1 expression was 83.3%. SP142 showed positive PD-L1 expression in 23 (62%) thymoma cases and eight (73%) thymic carcinoma cases. In contrast, SP263 antibody showed positive PD-L1 expression in 31 (84%) cases of thymoma and 9 (82%) cases of thymic carcinoma. In addition, type B thymomas exhibited significantly higher PD-L1 positivity than other thymoma types. The tumor-infiltrating lymphocytes were mostly CD3 and CD8 positive. No significant difference in overall survival was observed between the high and low PD-L1 expression groups in thymic carcinoma. Conclusion PD-L1 expression rate was high in TETs, with variations depending on the antibody used and histological subtype. SP263 showed higher PD-L1 expression compared to SP142. The type of the antibody used should be considered when evaluating PD-L1 expression in TETs.